Development and Impact Evaluation of an E-Learning Radiation Oncology Module - Alfieri, Joanne; Portelance, Lorraine; Souhami, Luis; Steinert, Yvonne; McLeod, Peter; Gallant, Fleure; Artho, Giovanni (International journal of radiation oncology, biology, physics, 2012)
Radiation oncologists are faced with the challenge of irradiating tumors to a curative dose while limiting toxicity to healthy surrounding tissues. This can be achieved only with superior knowledge of radiologic anatomy and treatment planning. Educational resources designed to meet these specific needs are lacking. A web-based interactive module designed to improve residents' knowledge and application of key anatomy concepts pertinent to radiotherapy treatment planning was developed, and its effectiveness was assessed. The module, based on gynecologic malignancies, was developed in collaboration with a multidisciplinary team of subject matter experts. Subsequently, a multi-centre randomized controlled study was conducted to test the module's effectiveness. Thirty-six radiation oncology residents participated in the study; 1920 were granted access to the module (intervention group), and 17 in the control group relied on traditional methods to acquire their knowledge. Pretests and posttests were administered to all participants. Statistical analysis was carried out using paired t test, analysis of variance, and post hoc tests. The randomized control study revealed that the intervention group's pretest and posttest mean scores were 35% and 52%, respectively, and those of the control group were 37% and 42%, respectively. The mean improvement in test scores was 17% (p < 0.05) for the intervention group and 5% (p = not significant) for the control group. Retrospective pretest and posttest surveys showed a statistically significant change on all measured module objectives. The use of an interactive e-learning teaching module for radiation oncology is an effective method to improve the radiologic anatomy knowledge and treatment planning skills of radiation oncology residents.